2010
DOI: 10.3961/jpmph.2010.43.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Concentrations of Organochlorine Pesticides and Metabolic Syndrome Among Non-Diabetic Adults

Abstract: Despite the small sample size, this study suggests that the background exposure to some OCPs may be associated with metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 18 publications
2
40
1
1
Order By: Relevance
“…Significant trends were observed in adjusted log 10 oxychlor, tNONA, HCB and β -HCCH models ( p = 0.056 in the latter) as well. Park et al (2010) found a positive association between β -HCCH and metabolic syndrome in their case-control study; ORs (95% CI) across tertiles 2 and 3 of the compound were 3.2 (1.0–10.3) and 4.4 (1.4–13.5) in a model adjusted for age, sex, alcohol and smoking. The ORs were greatly attenuated when BMI was added to that model and consistent with the effect estimates observed in the Anniston population.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Significant trends were observed in adjusted log 10 oxychlor, tNONA, HCB and β -HCCH models ( p = 0.056 in the latter) as well. Park et al (2010) found a positive association between β -HCCH and metabolic syndrome in their case-control study; ORs (95% CI) across tertiles 2 and 3 of the compound were 3.2 (1.0–10.3) and 4.4 (1.4–13.5) in a model adjusted for age, sex, alcohol and smoking. The ORs were greatly attenuated when BMI was added to that model and consistent with the effect estimates observed in the Anniston population.…”
Section: Discussionmentioning
confidence: 93%
“…Polychlorinated dibenzo-p-dioxins and polychlorinated dibenzo-furans also were linked to metabolic syndrome in a cross-sectional Taiwanese study (Chang et al, 2010). Associations between organochlorine compounds and metabolic syndrome were observed in a case-control study in Uljin County Korea (Park et al, 2010) and in a second case-control study (nested) from the same community-based cohort (Lee et al, 2014b). Increased organochlorine pesticide levels also have been observed in participants with metabolic syndrome in a small clinical study in India (Tomar et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Previous experiments have demonstrated that exposure to organochlorine pesticides might induce intrauterine growth retardation (IUGR) [38], [39] and obesity in puberty [47], [48], [49], [50]. Prenatal exposure to low doses of MXC reduces the postnatal growth [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that exposure to EDCs such as dioxins (39,42), bisphenol A (21), phthalates (37), or p,p=-dichlorodiphenyltrichloroethane (27,40) is highly associated with the increased risk of developing insulin resistance or diabetes, because the subpopulations that have the highest rates of these chronic diseases are also those have greatest exposure to EDCs.…”
mentioning
confidence: 99%